Extending the theory of planned behavior to predict the intention of telecardiology adoption in Malaysia - Yeo, Kee Jiar; Lee, Shih Hui; Rania Hussein Ahmed Al-Ashwal, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Telecardiology had emerged as a promising tool in cardiology to improve the overall services and prevent loss due to cardiovascular diseases. User acceptance is an important determinant for ensuring successful telecardiology implementation. Acceptance of telemedicine is usually indicated by the rate of diffusion throughout the healthcare system as well as the behavioural intention to use among the targeted population. This study examined factors influencing users’ intention for telecardiology usage. An extended Theory of Planned Behaviour model was utilised to assess the manner in which an individual’s personality traits and beliefs regarding telecardiology influenced their usage intention. This cross-sectional study involved a convenience sample of 423 healthcare receivers and providers of selected hospitals and a cardiac surgery centre in Malaysia. A questionnaire consisting of 46 items was used in data collection. The questionnaire was adapted and developed based on Theory of Planned Behaviour, Technology Acceptance Model and Technology Readiness Index. Structural equation modelling was performed for data analysis. The results underlined attitude, perceived behavioural control and subjective norm as significant determinants of intention. Meanwhile, perceived usefulness and perceived ease of use were the antecedents for the attitude towards telecardiology use. On the other hand, optimism is the only attribute that significantly influenced both perceived usefulness and perceived ease of use towards telecardiology use. The knowledge obtained from this study will allow policymakers and implementers to develop feasible strategies and effective interventions promoting telecardiology usage in Malaysia, combating against its underutilisation that typically leads to loss of time, money and effort.